2020
DOI: 10.1021/acs.jpcb.0c07280
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Dynamics and Thermally Activated Delayed Fluorescence in the Classic Electron Acceptor Tetracyanoquinodimethane

Abstract: Tetracyanoquinodimethane (TCNQ) is identified as one of the most important and classic constituents for the synthesis of organic conductors and shows an acute response of the fluorescence quantum yield to subtle changes in the polarity of solvents. Here, we report on characterization of the excited-state dynamics of TCNQ using time-resolved fluorescence and femtosecond transient absorption (TA) measurements in various solvents. Fluorescence decay and TA dynamics reveal that the fluorescence emissive and nonemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…On the other hand, femtosecond and nanosecond transient absorption spectra give detail information of both emissive and non-emissive states. [32][33][34][35][36][37][38] Pulsed laser excited time-resolved electron paramagnetic resonance (TREPR) spectroscopy is also an useful method, especially to detect the paramagnetic transient species in TADF, for instance the 3 CT and 3 LE states, as well as the ISC mechanisms. [26,[39][40][41] The topic has been summarized in a recent review article and a few research papers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, femtosecond and nanosecond transient absorption spectra give detail information of both emissive and non-emissive states. [32][33][34][35][36][37][38] Pulsed laser excited time-resolved electron paramagnetic resonance (TREPR) spectroscopy is also an useful method, especially to detect the paramagnetic transient species in TADF, for instance the 3 CT and 3 LE states, as well as the ISC mechanisms. [26,[39][40][41] The topic has been summarized in a recent review article and a few research papers.…”
Section: Introductionmentioning
confidence: 99%
“…However, these spectral methods (especially the former) only supply direct information about the bright (or emissive) excited states, such as the 1 CT state in electron donor‐acceptor type of TADF molecules, it gives no direct information about the dark (non‐emissive) states involved in the TADF processes, such as the 3 LE and 3 CT states (these states are usually non‐emissive in fluid solution at room temperature). On the other hand, femtosecond and nanosecond transient absorption spectra give detail information of both emissive and non‐emissive states [32–38] . Pulsed laser excited time‐resolved electron paramagnetic resonance (TREPR) spectroscopy is also an useful method, especially to detect the paramagnetic transient species in TADF, for instance the 3 CT and 3 LE states, as well as the ISC mechanisms [26,39–41] .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] They recently carried out transient absorption and uorescence spectroscopic studies and described the shorter uorescence lifetime in higher polar solvent to be due to the faster nonradiative decay to the nonuorescent state whose energy is lowered at higher polar solvent. 19 However, the non-uorescent state was not clearly assigned and they proposed a possibility of the triplet state. Despite these interesting excited-state characteristics in bulk system, gas-phase spectroscopic study of a neutral TCNQ molecule has not been performed until 2019, when we rst reported the S 1 (pp*; B 3u )-S 0 (A g ) electronic spectrum of TCNQ in a cold free jet by means of laser-induced uorescence (LIF) spectroscopy.…”
mentioning
confidence: 99%
“…Recent studies on photophysics have been performed in the gas phase, solutions, and polymer matrices. [13][14][15][16][17][18][19] We previously reported the fluorescence spectra of TCNQ in a variety of solvents. 15 Blue fluorescence of TCNQ was observed in nonpolar solvents, whereas the fluorescence quantum yield (QY) decreased significantly with an increase in solvent polarity.…”
Section: Introductionmentioning
confidence: 99%
“…15,17 The excited-state dynamics in various solvents were studied using femtosecond transient absorption (TA) and time-resolved fluorescence measurements. 13,19 The TA dynamics demonstrated that relaxation from an emissive locally excited (LE) state to a nonemissive state occurred within a few picoseconds in polar solvents. 13 Thermally activated delayed fluorescence (TADF) was also observed for carbon tetrachloride.…”
Section: Introductionmentioning
confidence: 99%